1995
DOI: 10.1152/ajpregu.1995.269.1.r173
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of men's responses to seasonal changes in day length by modern artificial lighting

Abstract: We recently reported that humans have conserved mechanisms, like those that exist in other animals, which detect changes in day length and make corresponding adjustments in the duration of nocturnal periods of secretion of melatonin and of other functions. We detected these responses in individuals who were exposed to artificial "days" of different durations. The purpose of the present study was to determine whether men who are exposed to natural and artificial light in an urban environment at 39 degrees N are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
5

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 0 publications
3
53
0
5
Order By: Relevance
“…On these occasions, the average times (± S.D.) of sunrise and sunset were 07.19 ± 00.10 h and 17.06 ± 00.18 h in winter and 05.51 ± 00.07 h and 20.33 ± 00.04 h in summer, respectively (for details see Wehr et al 1995a). …”
Section: Subjectsmentioning
confidence: 97%
See 2 more Smart Citations
“…On these occasions, the average times (± S.D.) of sunrise and sunset were 07.19 ± 00.10 h and 17.06 ± 00.18 h in winter and 05.51 ± 00.07 h and 20.33 ± 00.04 h in summer, respectively (for details see Wehr et al 1995a). …”
Section: Subjectsmentioning
confidence: 97%
“…Their compliance was monitored with sleep logs. Volunteers participated in five different studies, the details of which have been published elsewhere (Wehr et al 1993(Wehr et al , 1995aWehr, 1996;Aeschbach et al 1997Aeschbach et al , 1999. All research was consistent with the Declaration of Helsinki and was approved by the institutional review board of the Intramural Research Program of the National Institute of Mental Health (NIMH).…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial interest has developed in the general effects of disruption of this rhythmicity on health in man [40,41]. Human responses to seasonal changes in the natural photoperiod were more robust prior to the Industrial Revolution and have subsequently been increasingly suppressed by alterations in the physical environment [42,43]. Disruption of these processes is exemplified by the extreme circumstances of reversal of day/night working patterns seen in some shift workers.…”
Section: Man Diabetes and Cardiovascular Diseasementioning
confidence: 99%
“…Several studies from Wehr and collaborators 62 have suggested that modern men's use of artificial light after dark and artificial darkness during the daytime suppresses responses 63 to seasonal changes in the duration of the natural scoto-and photoperiod that might otherwise occur at a given latitude, producing a chronic disturbance in the sleep pattern and decreasing, overall, the total amount of sleep. It is difficult to conceive that chronic sleep deprivation in humans could be obtained and maintained without any activation in the stress axis.…”
Section: Chronic Sleep Deprivationmentioning
confidence: 99%